Relationship between Knowledge and Premaretal Sex Attitudes in Adolescents in Kalipuro 3 Public Middle School - Hanien Firmansyah; Ayik Mirayanti Mandagi (Universitas STRADA Indonesia, 2020)
The variables in this study are knowledge and premarital sex attitudes. Measurement of knowledge and attitudes is done by distributing questionnaires filled in by each student. Respondents of this study were all students totaling 84 students. Analysis of the data in this study using univariate analysis to see the description of respondents and bivariate analysis to see the relationship between knowledge variables with premarital sex attitudes. The results showed that the majority of respondents had poor knowledge of 39.3%. The attitude variable shows that the majority of respondents have a bad attitude towards premarital sex which is equal to 56%. A bad attitude is someone's attitude that leads to premarital sex. Bivariate analysis in this study shows the value of p <α (α = 0.05; CI = 95%) which means that there is a relationship between knowledge with premarital sex attitudes in adolescents